Optimal anti lock braking system with regenerative braking in hybrid electric vehicle - Dehghani, Dana (2014)
Hybrid electric vehicle is an electric drive vehicle which is powered by internal combustion engines (ICE) and an electric motor. However, this vehicle has some problems such as driving range, recharge time and battery cost. On the other hand, one advantage of HEV is able to recover energy during the brake by converting kinetic energy into electric energy and use it immediately or stored when it is required. This process is called regenerative braking. Anti-lock-braking system (ABS) is a safety system which allows the wheels to maintain the friction between the tires and prevent the car from skidding especially on dry and slippery road surfaces. Change in vehicle weight, friction coefficient of the road and road inclination can affect the behavior of the braking system. Therefore, optimization of the ABS system is necessary. In this study, optimal anti-lock-braking system (ABS) with regenerative braking in a hybrid electric vehicle is surveyed. The methodology consists of the mathematical model of the vehicle, ICE and electric motor, control design for ABS system and simulation. Besides, MATLAB software is used for the simulation model.